Sustaining the delivery of essential services among the ongoing coronavirus disease 2019 pandemic - Saurabh RamBihariLal Shrivastava (Muller Journal of Medical Sciences and Research, 2020)
The Corona Virus Disease-2019 (COVID-19) pandemic has produced a massive impact on the health care delivery system and on the daily routine of the general population. Owing to the massive load on the health sector due to the ongoing outbreak, most of the health systems have been stretched beyond their capacity and capability. This is not a good sign considering the fact that if the health system is exhausted, obviously the incidence of vaccine-preventable diseases and other treatable conditions will show a significant rise. In conclusion, amidst the ongoing battle against the COVID-19 pandemic, it is a must that the delivery of essential health services in the community is also sustained. Even though, it is a difficult ask from the health authorities, proper planning and awareness can definitely help us in the delivery of an accelerated response to COVID-19 and also not jeopardize the delivery of essential services.